Associations of Personality Traits With Chronic Low-Grade Inflammation in a Swiss Community Sample - Wagner, En-Young N.; Ajdacic-Gross, Vladeta; Strippoli, Marie-Pierre F.; Gholam-Rezaee, Mehdi; Glaus, Jennifer; Vandeleur, Caroline; Castelao, Enrique; Vollenweider, Peter; Preisig, Martin; von Känel, Roland (Frontiers in Psychiatry, 2019)
Objective: Among the major dimensions of personality, high Neuroticism and low Conscientiousness have frequently been linked to worse health-related behaviors and poor health outcomes. However, studies on the association between personality traits and biomarkers of chronic low-grade inflammation reflecting increased morbidity and mortality risk are sparse; therefore, the aim of this study was to explore this association. Methods: A population-based Swiss sample of 2,182 persons (40-82 years, 42% men) completed a comprehensive personality questionnaire (NEO Five-Factor Inventory-Revised). Circulating levels of inflammatory markers, including C-reactive protein, interleukin (IL)-1β, IL-6, tumor necrosis factor-α, and levels of the “cardioprotective” adipo(cyto)kine adiponectin were also determined. Analyses controlled for sociodemographic factors, traditional cardiovascular risk factors and lifetime psychiatric disorders using a validated semi-structured psychiatric interview. The role of gender as a moderator of the personality-inflammation link was additionally explored. Results: Controlling for all covariates, higher Extraversion (β=0.092, 95%CI 0.004-0.180) was positively associated with higher IL-6 levels, and higher Conscientiousness (β=-0.095, 95%CI -0.180-[-0.009]) were significantly associated with lower IL-6 levels (all p-values<0.05). Neuroticism and Agreeableness showed no significant association with any inflammatory biomarker. The associations between personality traits and inflammatory markers were not moderated by gender. Conclusions: Conscientiousness seems to be inversely related to chronic low-grade inflammation as measured by IL-6 levels, compatible with protection from the cardiovascular risk. The opposite may apply to Extraversion. Further research is needed to better understand the underlying mechanisms and their impact for health outcomes in the community.